Postponement of the 2024 Election: Failure to Create Policy Window from the Perspective of the Multiple Stream Framework - Fatkhuri Fatkhuri (JURNAL ILMU SOSIAL, 2023)
In late 2021, public attention was captivated by a contentious issue surrounding the potential postponement of the 2024 election. Prominent figures including Minister of Maritime Affairs and Investment Luhut Binsar Panjaitan, as well as leaders from the Golkar, PKB, and PAN parties, put forward proposals to delay the upcoming election. This study was undertaken to delve into the underlying factors contributing to the downfall of the discourse advocating the postponement of the 2024 election. Through the application of Kingdon's (2014) multi-stream framework (MSF) analysis, this research reveals that the notion of postponing the election lacked the necessary feasibility to transition into a viable policy agenda, as assessed from the perspectives of the problem stream, policy stream, and political stream. Examination of the problem stream reveals a lack of indicators supporting the idea of postponing the 2024 election from an economic standpoint. The prevalent positive economic growth and the optimistic sentiment of the populace toward national economic progress undermine any basis for endorsing the discourse. Moving to the policy stream, it becomes evident that most legislative members and community groups outright rejected the discourse. Additionally, the dearth of policy entrepreneurs emerged as a crucial factor contributing to the discourse's failure. Lastly, from the political stream perspective, the lack of widespread public support proved to be a pivotal factor in the discourse's demise. Political parties, the legislature, and various segments of society, including students, vehemently opposed the proposition. This landscape underscores the incongruence between the nation's sentiment and the notion of postponing the election. Consequently, the inability of the discourse to gain traction as a government policy agenda can be attributed to the prevailing economic conditions, the absence of substantial public support, and the lack of influential groups positioned as policy entrepreneurs advocating for the postponement of the 2024 election.